POLITICAL LITERACY RESEARCH: A HYBRID SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Mahmuda Aulia; Khairul Musrizal (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2026)
This study addresses the limited comprehensive investigations on political literacy despite the growing body of studies conducted over the past few decades. The research aims to provide an extensive understanding of global trends, conceptual foundations, and thematic structures related to political literacy through a systematic literature review and bibliometric analysis. Using the keyword “Political Literacy,” a total of 5,900 publications from 1978 to 2025 were retrieved from the Scopus database and analyzed using VOSviewer to visualize collaboration networks, author productivity, and thematic clusters across countries. The findings indicate that political literacy research is geographically diverse, with major contributions from the United Kingdom, China, and the United States, while emerging scholarly attention is evident in Turkey, Malaysia, Indonesia, and several developing nations. Core themes shaping the academic discourse include media literacy, civic engagement, democratic education, and conceptual development. The study underscores the importance of expanding political literacy research in underrepresented regions to promote global inclusivity and cross-cultural understanding. It further highlights the need to integrate political literacy within educational and civic frameworks to nurture informed, active, responsible, and participatory citizens. Overall, this review provides a comprehensive, evidence-based foundation for advancing sustainable political literacy education and guiding future interdisciplinary research.